2022
DOI: 10.3389/fnut.2022.940689
|View full text |Cite
|
Sign up to set email alerts
|

Addictive behavior and incident gallstone disease: A dose–response meta-analysis and Mendelian randomization study

Abstract: BackgroundPrevious studies have suggested associations between addictive behavior and gallstone disease (GSD) risk, yet conflicting results exist. It also remains unclear whether this association is causal or due to confounding or reverse associations. The present study aims to systematically analyze the epidemiological evidence for these associations, as well as estimate the potential causal relationships using Mendelian randomization (MR).MethodsWe analyzed four common addictive behaviors, including cigarett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Another Mendelian randomization study also supported a causality of gallstone disease incidence with lifetime smoking (OR=1.008; 95%CI: 1.003-1.013) and current smoking (OR=1.007; 95%CI: 1.002-1.011) [25]. In contrast, some other studies have failed to establish an association between smoking and developing gallstones.…”
Section: Discussionmentioning
confidence: 93%
“…Another Mendelian randomization study also supported a causality of gallstone disease incidence with lifetime smoking (OR=1.008; 95%CI: 1.003-1.013) and current smoking (OR=1.007; 95%CI: 1.002-1.011) [25]. In contrast, some other studies have failed to establish an association between smoking and developing gallstones.…”
Section: Discussionmentioning
confidence: 93%
“…A similar study assessed the risk of gallstone disease among a sample of the UK Biobank (including 10520 cases of gallstone disease), and a sample from the FinnGen consortium (including a sample of 11675 gallstone disease) according to the estimated genetic risk of type 2 diabetes, obesity, and specific lifestyle factors (cigarette smoking, and alcohol and coffee consumption). The study identified an increased risk of gallstone disease with BMI, waist circumference, diabetes, and smoking initiation, and a protective effect of coffee consumption against gallstone disease development [ 18 ]. Our investigation also identified a similar association between elevated BMI levels and smoking initiation and the increased risk of gallstone disease, and a protective effect of coffee intake against the development of gallstone disease.…”
Section: Discussionmentioning
confidence: 99%